Layout and Component Size Optimization of Sewer Network Using Spanning Tree and Modified PSO Algorithm - Praveen K. Navin; Yogesh P. Mathur (Water Resources Management, 2016)

OPTIMAL WATER SCHEDULING IN IRRIGATION CANAL NETWORK USING PARTICLE SWARM OPTIMIZATION - Anil W. Pawde; Yogesh P. Mathur; Rajesh Kumar (Irrigation and Drainage, 2013)
Rotational water scheduling in the irrigation canal network is a problem of preparing the operation schedule of lateral canals to deliver the required quantity of water to the irrigation fields under it within the rotational period as per the crop water requirement. The important objectives of a rotational canal schedule are to minimize capacity of canal and operational stages of the head gate of supply canal; subject to canal capacity constraint. In the present paper, to achieve these objectives, the decision variables considered are rate of water delivery and start time of delivery points, which are determined by the model within the specified range. Particle swarm optimization has been used to solve the problem and applied on the two water scheduling problems for generating the optimal water schedule. The schedules generated by the model shows that the inflow hydrographs of supply canals are approximately constant throughout the rotation period with least operation of canal head gate which could results in minimum conveyance losses. This model could be used for the preparation of a rotational schedule for the existing irrigation canal system and a more economic design of the supply canals for a new irrigation canal system. Copyright © 2013 John Wiley & Sons, Ltd.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)